Discovery of a novel HLA‐DRB1*04:05 variant, DRB1*04:05:15, in a Taiwanese and the probable HLA haplotype in association with DRB1*04:05:15. (17th April 2013) - Yang, K. L.; Lee, S. K.; Lin, P. Y.
Summary: Here, we report a novel HLA‐DRB1*04 allele, DRB1*04:05:15, found in a Taiwanese unrelated volunteer bone marrow hematopoietic stem cell donor by a sequence‐based typing (SBT) method. The DNA sequence of DRB1*04:05:15 is identical to the sequence of DRB1*04:05:01 in exon 2, except the nucleotide at the position 198 where C is substituted by T (TAC→TAT at codon 37). Due to the silent mutation, the nucleotide replacement generated no amino acid variation in comparison with DRB1*04:05:01. We postulate the allele DRB1*04:05:15 was probably derived from DRB1*04:05:01 via a nucleotide point mutation event. The probable HLA‐A, ‐B, ‐C, ‐DRB1 and ‐DQB1 haplotype in association with DRB1*04:05:15 may be deduced as A*02:01‐B*48:01‐C*08:03‐DRB1*04:05:15‐DQB1*04:01.